Invasive Mole Resulting in Uterine Rupture: A Case Report - Wu, Anshan; Zhu, Qiong; Tan, Chang; Chen, Long; Tao, Yin (Frontiers in Surgery, 2022)
A history of uterine surgery is a common cause of the uterine rupture. An invasive mole that leads to uterine rupture is rarely observed in the clinic. A 31-year-old woman who had no children, she abortion was performed 53 days after pregnancy. After the abortion, she still having abdominal pain and scanty vaginal bleeding. Then, text the serum human chorionic gonadotropin(HCG) was raised. An ultrasound examination and MR imaging revealed the uterus was enlarged and a mass in the myometrium. When the gynecologist prepares for treatment, the uterus ruptured cause the patient shocked. Eventually the patient removed the uterus and pathological result is the invasive mole.